ANALISIS KUALITAS WEBSITE MENGGUNAKAN METODE WEBQUAL 4.0 DI SMP NEGERI 3 LEKSONO - Jumadi Dwi Stiyanto; Saifu Rohman; Iman Ahmad Ihsanuddin (Tekompedia : Jurnal Ilmiah Ilmu Komputer, 2024)
The website is an important factor that is considered in an institution, especially education. Having a website is a picture of the progress of an educational institution. This is what makes researchers want to do research on the website at SMP N 3 Leksono. The purpose of this study was to determine the quality of the website where analysis and measurement had not previously been carried out in assessing the quality of the SMP N 3 Leksono website. The method used in this study is the WebQual 4.0 method and the object under study is the website at SMP N 3 Leksono. The number of respondents is 79 people who come from users, Students and Duru. Data collection techniques were carried out using a questionnaire. The variables used in this research are Usability, Information Quality, and Service Interaction Quality and Overall Impression on the website at SMP N 3 Leksono based on the WebQual 4.0 questionnaire method with 23 attribute items. The results obtained from the website quality analysis have a percentage of 71.25% of respondents' opinions agree. Based on the interpretation value of website user questionnaires, it can be concluded that website quality provides user convenience and satisfaction..